Design of a stirred tank type bioreactor for the growth of Rhodococcus opacus - Bogantes-Portuguez, Pablo (2022)
This article presents the design of a microcontroller-assisted stirred tank bioreactor using concepts of simplicity of use, modularity, aesthetics, and ergonomics, according to the needs of the Cibus 3.0 company. The tank has three main parts: lid (it has its elements according to its use); sensor box (device that uses pH sensors, temperature, and turbidity of the medium); and tank (with a volumetric capacity of 21.5 L). A generic handheld vaporizer was attached as a method of in situ sterilization. To evaluate the efficiency of sterilization, surface samplings were carried out in the most critical areas of biofilm formation (lid, tubes, wall, impeller, and arrow), after fermentations of E. coli and R. opacus. The steam engine shown not to meet the goal of eliminating contamination, achieving 92% sterilization. However, the use of an autoclave allowed the expected sterilization performance, this was verified when simulating fermentation with sterile medium and not presenting contamination at the end of the test. The possibility of using pH, suspended solids and temperature sensors was determined, taking part of the medium for each repetition without contaminating of the system. In this way, a device capable of taking measurements by means of a microcontroller is introduced. To corroborate the functionality of the designed equipment, three fermentations were carried out with the R. opacus bacteria, where growth curves were obtained validating the operation of the design around the user and the process.